Alkylated polycyclic aromatic hydrocarbons are the largest contributor to polycyclic aromatic compound concentrations in traditional foods of the Bigstone Cree Nation in Alberta, Canada. (15th April 2021) - Golzadeh, Nasrin; Barst, Benjamin D.; Baker, Janelle M.; Auger, Josie C.; McKinney, Melissa A.
Abstract: Rising global demand for energy promotes extensive mining of natural resources, such as oil sands extractions in Alberta, Canada. These extractive activities release hazardous chemicals into the environment, such as polycyclic aromatic compounds (PACs), which include the parent polycyclic aromatic hydrocarbons (PAHs), alkylated PAHs, and sulfur-containing heterocyclic dibenzothiophenes (DBTs). In areas adjacent to industrial installations, Indigenous communities may be exposed to these PACs through the consumption of traditional foods. Our objective was to evaluate and compare the concentrations of total PACs (∑PAC), expressed as the sum of the 16 U.S. EPA priority PAHs (∑PAH), 49 alkylated PAHs (∑alkyl-PAH), and 7 DBTs (∑DBT) in plant and animal foods collected in 2015 by the Bigstone Cree Nation in Alberta, Canada. We analyzed 42 plant tissues, 40 animal muscles, 5 ribs, and 4 pooled liver samples. Concentrations of ∑PAC were higher in the lichen, old man's beard ( Usnea spp.) (808 ± 116 ng g −1 w.w.), than in vascular plants, and were also higher in smoked moose ( Alces alces ) rib (461 ± 120 ng g −1 w.w.) than in all other non-smoked animal samples. Alkylated-PAHs accounted for between 63% and 95% of ∑PAC, while the concentrations of ∑PAH represented 4%–36% of ∑PAC. Contributions of ∑DBT to ∑PAC were generally lowest, ranging from <1% to 14%. While the concentrations of benzo(a)pyrene (B[a]P) and ∑PAH4 (∑benzo[a]anthracene, chrysene, benzo[b]fluoranthene, and B[a]P) in all samples were below guideline levels for human consumption as determined by the European Commission, guideline levels for the more prevalent alkylated PAHs are not available. Given the predominance of alkylated PAHs in all food samples and the potentially elevated toxicity relative to parent PAHs of this class of PACs, it is critical to consider a broader range of PACs other than just parent PAHs in research conducted close to oil sands mining activities. Graphical abstract: Image 1 Highlights: Benzo[a]pyrene (B[a]P) was not detected in most of the plant and animal samples. Alkylated PAHs were the dominant PAC class in all plant and animal samples. Old man's beard (a lichen) and smoked moose rib had the highest levels of alkylated PAHs. Levels of dibenzothiophenes (DBTs) were minor contributors to the total PACs. Abstract : Alkylated PAHs were the dominant class of PACs relative to parent PAHs and DBTs in traditional foods of the Bigstone Cree Nation near the Athabasca oil sands in Alberta, Canada.